The first Middle Jurassic Protobrachyceron Handlirsch fly (Diptera: Brachycera: Protobrachyceridae) from Inner Mongolia (China) - Zhang, Kuiyan; Yang, Ding; Ren, Dong (Zootaxa, 2008)
Protobrachyceridae, which is an archaic representative of the Brachycera with only one known genus and two species, Protobrachyceron liasinum Handlirsch, 1920 and P. zessini Krzeminski & Ansorge, 2000, has been described from the lower Toarcian of Germany. The family can be distinguished by the following characters: vein Sc ending at midwing, both vein R4 and cell d distinctly shorter than vein M1 in length, vein CuP well visible, mouth of cell r1 narrow, five posterior cells widely open, cells m3 and cup narrowly open.